Collaborative learning: a strategy that humanizes education - Vargas, Kleiber (2020)
The investigation had the purpose of verifying the influence of the collaborative learning strategy on the achievement of cognitive, procedural and attitudinal performance and learning. Being the quasi-experimental study oriented to the study of cause relationships between the variables in question and thus describe and explain the phenomena found. To support the research, an explanatory quantitative methodology was used that allowed us to conclude that collaborative learning positively influences the achievement of cognitive, procedural and attitudinal learning. The results show that 85.18% of students increased their scores for unit II compared to unit I. It is a strategy that contributes to the humanization of the educational system and with it would banish the concept of "academic solitude". However, an individualistic education that removes the human sensitivity of the students, what it sees is the stratification of groups that elitize and dehumanize education. Well, the idea of meritocracy and competitiveness generates in the apprentices the idea of "as long as I am well, the rest does not matter".